Faktor-Faktor yang Mempengaruhi Willingness to Pay Konsumen terhadap Produk Wedang Uwuh Instan CV Dewi Makmur - Oktiana, Filaeily Ardhita; Sadiyah, Fitria Naimatu; Rahayu, Novia Aristi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aimed to analyze the value of consumers’ willingness to pay for the Instant Wedang Uwuh product produced by CV Dewi Makmur. The product was an innovative traditional herbal drink presented in an instant form, making it more practical to serve. The research was conducted using a quantitative approach, utilizing both primary and secondary data obtained through direct observation and the distribution of questionnaires to prospective consumers. The method used to determine the willingness to pay value was the Contingent Valuation Method (CVM), an economic valuation approach based on consumers’ perceptions of the product, using an open-ended question technique. To analyze the influencing factors and test hypotheses, logistic regression was applied with the aid of the Statistical Package for the Social Sciences (SPSS) version 25.0. The results showed that consumers’ willingness to pay for the Instant Wedang Uwuh product reached IDR 25,190 per product or per box containing 5 sachets, each weighing 25 grams. This value was 26% higher than the previously offered selling price of around IDR 20,000. The factor found to have a significant influence on willingness to pay was the product quality variable, indicating the potential for increasing the market selling price while maintaining product quality.